Automatic rabbit feeder / Muhammad Amirul Aiman Mohd Noor, Muhammad Faiz Zakaria and Muhammad Nashrul Wafid Muhammad - Mohd Noor, Muhammad Amirul Aiman; Zakaria, Muhammad Faiz; Muhammad, Muhammad Nashrul Wafid (2015)
Automatic rabbit feeder is the machine that useful for farmer to feed their breed of rabbits or pets.This machine consists Arduino, Real Time Clock(RTC), Liquid Crystal Display(LCD), stepper motor, relay, potentiometer, switch, and battery 12V. This machine is very useful compatible with their busy lifestyle and can be adapted in this community nowadays. This machine used a simple circuit that can control the motor to feed the breed of rabbits which set the timer by coding the arduino but it depends to the RTC time. The timer of the machine already set 3 times per day by coding the Arduino which the motor will turn on. The timer 0800, 1200, 2000 already set by coding the Arduino to feed the breed of rabbits.This machine applied by AC supply that the maintainances of the circuit to work as well. The AC supply directly connected to the arduino for turn on. The RTCapplied by battery 12V to turn on the RTC circuit. The motor will turn on when 0800 and offafter 10 minutes. This machine suitble as a choice for people to solve the problem to feed theirbreed of rabbits who has a busy lifesytle. In other meaning, they do not have to worry in arranging time to feed the breed of rabbits and just rely on this machine.